Synthesis and photoluminescence properties of Dy3+ doped white light emitting CdTa2O6 phosphors - EKMEKÇİ, METE KAAN (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2015)
The undoped and CdTa2O6:Dy3+ (0.2 <= x <= 2.0 mol%) phosphors were synthesized at 1100 degrees C for 12 h by the conventional solid state reaction method. The synthesized CdTa2O6:Dy3+ phosphors were characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Energy dispersive spectroscopy (EDS) and Photoluminescence (PL) analyses. The PL spectra showed the presence of excitation peaks between 310 and 440 nm due to the 4f-4f transitions of Dy3+. The emission of Dy3+ ions at 353.0 nm excitation was observed at 487.1 nm (blue) and 577.8 nm (yellow) due to the F-4(9/2)-> H-6(15/2) transitions and F-4(9/2)-> H-6(13/2) transitions, respectively. The PL analysis results also showed that the emissions increase with the increasing Dy3+ ion content. The emissions increased with the doping concentration of up to 1 mol%, and above this level decreased due to concentration quenching effect. The CIE chromaticity color coordinates (x,y) of the CdTa2O6:Dy3+ phosphors were found to be in the white light region of the chromaticity diagram. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: CdTa2O6; XRD-SEM; Dy3+; Photoluminescence; W-LEDs; LUMINESCENCE PROPERTIES; CRYSTAL-CHEMISTRY; SPECTROSCOPIC PROPERTIES; CHARGE COMPENSATION; QUANTUM DOTS; BATA2O6; PHASE